Improving Outcomes In Hemodialysis Patients: Collaborative Care Approaches For Medical Nurses (Journal of Namibian Studies : History Politics Culture, 2022)
Hemodialysis is a life-saving therapy for patients with end-stage renal disease (ESRD), but it presents complex challenges that require a multidisciplinary approach for optimal management. This article explores collaborative care approaches for medical nurses aimed at enhancing outcomes in hemodialysis patients. It examines the importance of teamwork, effective communication, and coordination among healthcare professionals involved in the care of hemodialysis patients. Additionally, it discusses key strategies and interventions that medical nurses can implement within the context of a collaborative care model to improve patient outcomes, including medication management, symptom assessment, patient education, and psychosocial support. By fostering collaboration and integrating various healthcare disciplines, medical nurses can play a vital role in optimizing the care and outcomes of hemodialysis patients.